Pulse wave parameters as a predictor of the development of post-transplant diabetes mellitus after kidney transplantation - Dominika Macakova; Josef Zadrazil; David Karasek; Veronika Kucerova; Katerina Langova; Lubica Cibickova (BMC Nephrology)
Abstract Background Kidney transplantation is the preferred treatment for patients with end-stage renal disease, significantly preserving kidney function and patient quality of life. However, post-transplant diabetes mellitus (PTDM) is a common complication, occurring in approximately one-third of renal transplant recipients. This study aims to evaluate the role of pulse wave parameters in predicting PTDM and to identify other pre-transplant risk factors. Methods This prospective cohort study included 105 patients on the kidney transplant waiting list from 2017 to 2022. Exclusion criteria included any pre-existing diabetes mellitus. Patients underwent physical examinations, laboratory analyses, and pulse wave analysis before transplantation and one year post-transplant. PTDM diagnosis followed International Consensus Guidelines. Data were analyzed using Wilcox test, Bonferroni correction, May-Whitney U-test, and Fisher’s exact test, with p < 0.05 considered statistically significant. Results Post-transplant, 21% of patients were diagnosed with PTDM, increasing to 35% 3months post-transplant and 43% at one year post-transplant. Significant findings included: Pre-transplat risk factors for developing PTDM: Proteinuria (p = 0.037, OR = 3.942) and perioperative hyperglycemia (p = 0.003, OR = 4.219 at 3 months; p = 0.001, OR = 4.571 at 1 year). Pulse wave parameters for developing PTDM: Pre-transplant Aortic PP > 45 mmHg (AUC = 0.757) and PWV > 8.5 m/s (AUC = 0.730) were strong predictors of the development of PTDM after 3 months (p < 0.0001). Moreover, we found significant improvements in aortic pulse pressure (Aortic PP) and pulse wave velocity (PWV) post-transplant (p < 0.0001). Conclusion Our study confirms that pulse wave parameters, such as Aortic PP and PWV, are significant predictors of PTDM in kidney transplant recipients (KTR). These findings support incorporating pulse wave analysis into routine pre-transplant evaluations to identify high-risk patients. Additionally, monitoring these parameters post-transplant may aid in early intervention and prevention of PTDM, ultimately improving patient outcomes. Trial registration Ethical approval was obtained from the Ethics Committee of Medical faculty and University Hospital Olomouc (approval no. 94/15).